Communication and authority with a partially informed expert. - Agastya, Murali; Bag, Parimal Kanti; Chakraborty, Indranil (RAND Journal of Economics (Wiley-Blackwell))
A sender-receiver game a la Crawford-Sobel is analyzed where the sender has expertise on some but not all the payoff-relevant factors. This residual uncertainty can either improve (even allow full revelation) or worsen the quality of transmitted information depending on a statistic called the effective bias. For symmetrically distributed residual uncertainty or quadratic loss functions, (i) the quality of information transmission is independent of the riskiness of residual uncertainty, (ii) it may be suboptimal to allocate authority to the informed player, (iii) despite players' preferences being arbitrarily close, it is impossible to assert that the receiver prefers delegation over authority or vice versa.